A single-blind, randomised controlled trial of StrataXRT® – A silicone-based film-forming gel dressing for prophylaxis and management of radiation dermatitis in patients with head and neck cancer. (October 2019) - Chan, Raymond J.; Blades, Rae; Jones, Lee; Downer, Tai-Rae; Peet, Samuel C.; Button, Elise; Wyld, David; McPhail, Steven; Doolan, Melissa; Yates, Patsy
Highlights: Many prophylactic/management interventions are available for radiation dermatitis. No effective topical treatment has shown effectiveness except for corticosteroids. A silicone-based film forming gel dressing (StrataXRT®) has become available. StrataXRT® is effective for preventing, and reducing grade 2 and 3 skin toxicity. Abstract: Aim: Investigate the effects of StrataXRT® versus 10% Glycerine (Sorbolene cream) for preventing and managing radiation dermatitis in patients with head and neck cancer receiving radical radiotherapy (≥50 Gy) with or without chemotherapy or biotherapy. Methods: A single-blind, randomised controlled, superiority trial was conducted. Patients either received StrataXRT® or Sorbolene (usual care). Skin toxicity, pain, itching and skin-related quality of life scores were collected from baseline, and up to four weeks post-treatment. Results: A total of 197 patients were randomised into the study. Skin toxicity was dependent on the treatment group with StrataXRT® patients experiencing lower mean skin toxicity at the end of the radiation treatment ( P  = 0.002). At the end of treatment, the StrataXRT® arm had a lower percentage of grade 2 (80%) and grade 3 (28%) skin toxicity compared to the sorbolene arm (91% and 45% respectively). After adjustment for Cetuximab, the StrataXRT® arm had a 12% lower risk of experiencing grade 2 skin toxicity (RRR = 0.876, 95% CI: 0.778–0.987, P  = 0.031); and a 36% lower risk of experiencing grade 3 skin toxicity (RRR = 0.648, 95% CI: 0.442–0.947, P  = 0.025). Cox regression analysis showed that patients receiving StrataXRT® had a 41.0% and 49.4% reduced risks of developing grade 2 and 3 skin toxicity respectively throughout treatment compared to the Sorbolene arm. There were no differences between groups in patient-reported outcomes. No treatment interruptions and study product related adverse events were reported in either arm. Conclusion: StrataXRT® is effective for preventing, and delaying the development of grade 2 and 3 skin toxicity. Trial registration: ACTRN12616000511437.